Ideologi Tafsir Era Reformasi - Yasif Maladi; Zulfadhli Rizki Barkia (Jurnal Iman dan Spiritualitas, 2021)
The study of interpretation in Indonesia is always experiencing developments. Various ideologies have sprung up in the study of interpretation, both classical and contemporary. In Indonesia, renewal in tafsir's study began to be crowded at the beginning of independence. When the emergence of interpretive works with various methods and styles, interpretation was very diverse, both in Arabic and Indonesian. The interpretation of thought influenced by Islamic ideology during the Reformation period was the scientific interpretation, the maudhu'i interpretation, and the hermeneutic approach. The al-Qur'an method used by the commentators varies because the study of the interpretation itself is prosperous. This research uses qualitative research. This type of research is library research, which discusses reformist Islamic ideology in interpretation. This study found that the Islamic ideology of the Reformation era liked the maudhu'i method of interpretation. Using this method, the moral messages of the Al-Qur'an, the interpreters very quickly conveyed the Al-Quran instructions to Muslims. We cannot separate the hermeneutic approach to Islamic ideology of Reformation from the hermeneutic approach in the study of interpretation. This approach is to assist the interpretation of the Qur'an which is used by the mufassir because of the complexities faced by the Indonesian Muslim community itself.